2009
DOI: 10.1590/s0103-21002009000600003
|View full text |Cite
|
Sign up to set email alerts
|

Mensuração e características de dor após cesárea e sua relação com limitação de atividades

Abstract: Objectives: To measure and characterize post cesarean section pain and to verify its relationship with limitations of physical activities. Methods: Descriptive study with 60 women in the post-operative period of cesarean section. Pain was measured with both the Numeric Scale and the McGill Pain Questionnaire. Limitations of physical activities were measured with a specific instrument developed for the study. Results: Sitting down and stranding up were the physical activities with the highest pain scores. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 21 publications
0
15
0
14
Order By: Relevance
“…Destaca-se que grande parte da insatisfação esteve relacionada à intensidade da dor durante o TP e parto no parto vaginal e no PP na cesariana, denotando que independente da via de parto a dor esteve presente em diferentes momentos do processo. Estudos anteriores identificaram que de forma geral, as mulheres mostraram-se insatisfeitas com a intensidade de dor sentida durante o TP (72,1%) 15 e no PP 10 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Destaca-se que grande parte da insatisfação esteve relacionada à intensidade da dor durante o TP e parto no parto vaginal e no PP na cesariana, denotando que independente da via de parto a dor esteve presente em diferentes momentos do processo. Estudos anteriores identificaram que de forma geral, as mulheres mostraram-se insatisfeitas com a intensidade de dor sentida durante o TP (72,1%) 15 e no PP 10 .…”
Section: Discussionunclassified
“…Contrariamente ao estudo realizado por Capogna et al 12 , os descritores mais citados (≥50%) foram ligados a sensações físicas: "cólica, queimação, pressionante, fincada, pesada, dolorida, cansativa-exaustiva e insuportável", sendo que o questionário foi aplicado no TP, o que sugere a diferença na escolha dos descritores. Souza et al 10 encontraram relatos de dor que "incomoda", "que prende" e "que repuxa" exclusivamente após a cesariana, utilizando o questionário de McGill em sua forma completa.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Hence, they are subject to greater incision pain. 10 In our daily professional practice, we have observed that post-Caesarean pain complaint have not always received proper attention, as each caregiver's sensitivity may vary according to the importance and value (s)he attributes to the other person's pain.…”
Section: Introductionmentioning
confidence: 99%